Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) Merek AQUA di Kota Malang (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang) - Ririn Maulidah; Ronny Malavia Mardani; Muhammad Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study was to determine and analyze the effect of product quality, price and promotion on purchasing decisions of AQUA brand Bottled Drinking Water (AMDK) in Malang City. Sampling was carried out on active S1 students at the Faculty of Economics & Business, Islamic University of Malang for the 2019/2020 academic year using the Malhotra formula so that a sample of 100 respondents was obtained. This research method uses multiple linear regression analysis with the SPSS analysis tool. This study shows that product quality, price and promotion have a simultaneous effect on purchasing decisions. Tests carried out with partial tests, all independent variables have a significant positive effect on the dependent variable.Keywords: Product Quality, Price, Promotion, Purchase Decision, AQUA Brand Bottled Drinking Water (AMDK).